Investigation of a discrete dynamical system in the vicinity of quasi-periodic trajectory - Samoilenko , A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study a discrete system in a neighborhood of a quasi-periodic trajectory. We obtain conditions for reducing a system in this neighborhood to a system with quasi-periodic coefficients. We determine the behavior of this system under the action of small perturbations.